Patient empowerment, what does it mean for adults in the advanced stages of a life-limiting illness: A systematic review using critical interpretive synthesis. (September 2018) - Wakefield, Dominique; Bayly, Jo; Selman, Lucy Ellen; Firth, Alice M; Higginson, Irene J; Murtagh, Fliss EM
Background: Patient empowerment, defined as 'a process through which people gain greater control over decisions and actions affecting their health' (World Health Organization) is a key theme within global health and social care strategies. The benefits of incorporating empowerment strategies in care are well documented, but little is known about their application or impact for patients with advanced, life-limiting illness(s). Aim: To identify and synthesise the international evidence on patient empowerment for adults with advanced, life-limiting illness(s). Design: Systematic review (PROSPERO no. 46113) with critical interpretive synthesis methodology. Data sources: Five databases (MEDLINE, Embase, CINHAL, PsycINFO and Cochrane) were searched from inception to March 2018. Grey literature and reference list/citation searches of included papers were undertaken. Inclusion criteria: empirical research involving patients with advanced life-limiting illness including descriptions of, or references to, patient empowerment within the study results. Results: In all, 13 papers met inclusion criteria. Two qualitative studies explored patient empowerment as a study objective. Six papers evaluated interventions, referencing patient empowerment as an incidental outcome. The following themes were identified from the interpretive synthesis: self-identity, personalised knowledge in theory and practice, negotiating personal and healthcare relationships, acknowledgement of terminal illness, and navigating continued losses. Conclusion: There are features of empowerment, for patients with advanced life-limiting illness distinct to those of other patient groups. Greater efforts should be made to progress the empowerment of patients nearing the end of their lives. We propose that the identified themes may provide a useful starting point to guide the assessment of existing or planned services and inform future research.